Biomonitoring agent for heavy metals run off from acid sulfate soil of aquaculture industries in Selangor, Malaysia - Othman, Rashidi; Mohd Hatta, Farah Ayuni; Shafiai, Shahima (Maxwell Scientific Organization, 2012, 2014)
The disturbance of acid sulfate soils due to poor wastewater management of aquaculture activities caused a major environmental issue such as metal pollution in coastal regions of many countries over the world. Peninsular Malaysia also challenged the same problem where it lost 18700 ha of coastal lowlands from 1980-1990. This activity caused the oxidation of pyrite which produces high concentrations of ferrous ions and sulfuric acid in turn attacks clay minerals and produces high concentrations of monomeric Aluminum (Al) and other acid-soluble metals. Subsequent leaching of these toxic products into adjacent water bodies is rapidly increasing the stress on ecosystems. Therefore, the research was aimed to monitor heavy metal runoff from acid sulfate soil at shrimp aquaculture areas through phytotechnology approach. The study was conducted at fourteen different sites in Selangor which contains large amount of acid sulfate soil. The result showed that Pistia stratiotes was substantially the best phytoindicator for Al, Iron (Fe) and Manganese (Mn) toxicity followed by Lemna minor, Nymphaea stellata and Urticulata aurea. On the other hand, N. stellata was observed to be best phytoindicatorfor Nickel (Ni) whereas for Arsenic (As) was Ludwigia palustris. Among these six species, the most potential biomonitoring agent to indicate acid-soluble metals are P. stratiotes and N. stellataas they are presence in low D.O level, high pH, high concentration of ammonium and tolerance to Al, Fe, Mn and Ni.